Data for: The circular economy potential of urban organic waste streams in low- and middle-income countries - Ddiba, Daniel; Andersson, Kim; Rosemarin, Arno; Schulte-Herbrüggen, Helfrid; Dickin, Sarah (Royal Institute of Technology, 2021)
This dataset includes the research data and supporting information for the publication "The circular economy potential of urban organic waste streams in low- and middle-income countries" which was published in the Journal of Environment, Development and Sustainability (DOI: 10.1007/s10668-021-01487-w).

This dataset and the associated publication are the basis upon which the REVAMP (Resource Value Mapping) tool has been developed. See more info about the REVAMP tool here: https://www.sei.org/revamp

Funding for this work came from the Swedish International Development Cooperation Agency (Sida) and the Swedish
Ministry of Environment through core support to SEI for the initiative on Sustainable Sanitation (www.sei.org/sustainable-sanitation) as well as the Swedish Research Council Formas through project grant number 2017-00268 to the UrbanCircle (Urban Waste into Circular Economy Benefits) project (www.sei.org/urbancircle).
Keywords: Resource recovery; Waste reuse; Sustainable sanitation; Waste management; Faecal sludge management; Civil Engineering; Samhällsbyggnadsteknik